User Profile-based Service Discovery for eHealth. - Tegegne, Tesfa; Kanagwa, Benjamin; van der Weide, Theo (My University, 2011)
PersonalizationisnotverycommoninService-orientedArchitectureandServicediscoveryinpractice,yet veryimportantasitenablestofindmorespecificandrelevantservices.Thisisespeciallytrueinthecaseof complexservice,wherethesystemtriestofindanoptimalcombinationsofservicesthattogethercansatisfya (complex)request.Wedescribetherelationbetweenpersonalizationandservicediscoveryingeneral,andthen concretizethisintheproposedServiceDiscoveryFramework(SDF).Personalizationeffectivelyimprovesthe qualityofthediscoveryalgorithminSDF.Asanapplication,weshowitsbenefitsinthecontextofeHealth
Keywords: Personalization; eHealth; Service Discovery; SOA.